Response of SDOF system to non-stationary earthquake excitation. - Jangid, R.S.
Earthquake excitation is often modelled by non-stationary random process (i.e. uniformly modulated broad-band excitation) for analysis of structural safety subjected to seismic hazards. In this paper, the non-stationary response of a single degree of freedom (SDOF) system to non-stationary earthquake motion is investigated for different shapes of modulating functions. The evolutionary power-spectral density function (PSDF) of the displacement of the SDOF system is obtained using the time varying frequency response function and the PSDF of the earthquake excitation. The close form expressions for time varying frequency response function are derived for different shapes of the modulating functions. In order to study the effects of the shape of the modulating function, a comparison of the non-stationary earthquake response of the SDOF system is also made for different modulating functions having the same energy content.
Keywords: SDOF system; Non-stationary.; Earthquake; Modulating function